Contribuição das forças biomecânicas na destruição periodontal. Estudos in vitro e in vivo - Nogueira, Andressa Vilas Boas [UNESP] (2014)
Several studies have been conducted to understand the effects of periodontal disease and orthodontic tooth movement on periodontal tissues, but the effects of both processes present together have not been fully elucidated. The aim of these in vitro and in vivo studies was to investigate the interactions of microbial and biomechanical signals in models that mimic the influence of orthodontic mechanical forces on the progression of periodontal disease and tissue destruction. In the in vitro study, human periodontal ligament cells (hPDL) were treated according to the following groups: Group I- cells without stimulation, II: cells stimulated with inactivated bacterium Fusobacterium nucleatum ATCC 25586, III and IV: cells subjected to cyclic tensile strain (CTS) of low (III) and high (IV) magnitudes, V and VI: cells stimulated with F. nucleatum ATCC 25586 and subjected CTS of low (V) and high (VI) magnitudes. The in vivo study was composed of 144 rats that were divided into four groups: 1- control group (C), 2- ligature-induced periodontal disease (P), 3- orthodontic movement (OM), and 4- P followed by OM (OMP). Periodontal disease was induced 5 days before orthodontic appliances placement and after 1, 3, 7, and 15 days of OM induction, animals were sacrificed. Expression of cytokines and their receptors was evaluated by PCR array, and the 6 most expressed inflammatory mediators had their results validated by real time PCR. Hemimaxillas blocks were used for bone volume fraction analysis by micro-computed tomography. The results of the in vitro study demonstrated that hPDL cells are able to produce visfatin and F. nucleatum significantly increased this production. After microbial and mechanical co-stimulation, there was a significant reduction in 18 the expression and synthesis of visfatin and significant increase in the expression and production of COX2 and PGE2...(Complete abstract eletronic acess below)